Residue handling and soil disturbance of an inclined time furrow opener - Borlagdan, Paterno C. (Philippine Engineering Journal)
A vertical and an inclined tine-furrow opener, with 30-degree angle of inclination with respect to the vertical axis perpendicular to the toll-bar, were compared and evaluated at different rake angles (60 degrees, 75 degrees, 90 degrees and 105 degrees) in terms of residue handling and soil disturbance. Three straw conditions were used namely: 1) standing rice stubbles without cut straw, 2) standing stubbles with wet cut straws and 3) standing stubbles with dry cut straws. The thirty-degree tine with 60 degrees rake angle has the best residue handling capability but with lifting effect on soil. Inclined tine with 90 degrees rake angle has a neutral soil working effect. The residue handling capability of the vertical and inclined tine decreases as the rake angle increases. Soil lifting effect was apparent at rake angles less than 90 degrees. At rake angles greater than 90 degrees there was soil compression.